The Impact of Financial Technology (Fintech) on Financial Inclusion in Developing Countries: A Critical Literature Analysis - Faqrurrowzi, Lendra; Pulungan, Delyana Rahmawany; Wahyudi Maherza (CERED Indonesia Institute, 2025)
Abstract This study examines how fintech is opening up access to financial services for marginalized communities in developing countries. Through a systematic literature review, we analyze how innovations such as digital wallets, peer-to-peer lending, and digital banking are changing the landscape of financial inclusion. Findings suggest that fintech plays a significant role in addressing geographic and cost barriers, but its effectiveness depends on digital infrastructure, supportive regulations, and the digital literacy level of the population. Despite its promise, the digital divide and data security remain major challenges. The results of this study offer valuable insights for policymakers and practitioners in designing strategies that maximize fintech's potential to expand financial access while minimizing its risks.